The Correlation between Fat Consumption and Atherogenic Index on Type 2 Diabetes Melitus Patients in dr. Soebandi Hospital - Mega Ratnasari; Ali Santosa; Dwita Aryadina Rahmawati (Journal of Agromedicine and Medical Sciences, 2018)
One of the risk factor that can be changed in type 2 diabetes melitus is food consumption. Fat is one of the macronutrients that have significant influence in consumption. Unhealthy diet can be a trigger to macrovascular complication that is coronary heart disease (CHD) which started with atherosclerosis. Atherogenic index is a good predictor for CHD. This study aims to determine the correlation between fat consumption with atherogenic index in DMT 2 patients at RSD dr. Soebandi. This is an analitic observational study with cross sectional design, using 74 type 2 diabetes melitus patients from Internal Poly at RSD dr. Soebandi who met inclusion and exclusion criteria. Fat consumption were obtained with 24-hours food recall interview and atherogenic index were obtained from TG and HDL levels in medical record. The average of fat consumption is 34,01% and as much 33 subjects (44,6%) have high risk of CHD (AI>0,21). Spearman correlation test between fat consumption with atherogenic index is p=0,025 which mean there is significant correlation between fat consumption and atherogenic index in type 2 diabetes melitus patients at RSD dr. Soebandi Keywords: DM Type 2, fat consumption, carbohydrate consumption, atherogenic index